Relação entre sintomas depressivos e a funcionalidade familiar de idosos institucionalizados - Oliveira, Simone Camargo de; Santos, Ariene Angelini dos; Pavarini, Sofia Cristina Iost (Revista da Escola de Enfermagem da USP, 2014)
The present study aimed to investigate the relationship between family functioning and depressive symptoms among institutionalized elderly. This is a descriptive, cross-sectional study of quantitative character. A total of 107 institutionalized elderly were assessed using a sociodemographic questionnaire, the Geriatric Depression Scale (to track depressive symptoms) and the Family APGAR (to assess family functioning). The correlation coefficient of Pearson’s, the chi-square test and the crude and adjusted logistic regression were used in the data analysis with a significance level of 5 %. The institutionalized elderly with depressive symptoms were predominantly women and in the age group of 80 years and older. Regarding family functioning, most elderly had high family dysfunctioning (57 %). Family dysfunctioning was higher among the elderly with depressive symptoms. There was a significant correlation between family functioning and depressive symptoms. The conclusion is that institutionalized elderly with dysfunctional families are more likely to have depressive symptoms.